A functional coefficient model view of the Feldstein-Horioka puzzle - Helmut Herwartz; Fang Xu (Kiel University, Department of Economics, 2007)
What does the saving-investment (SI) relation really measure and how should the (SI) relation be measured? These are two of the most discussed issues triggered by the so called Feldstein-Horioka puzzle. Based on panel data we introduce a new variant of functional coefficient models that allow to separate long and short to medium run parameter dependence. We apply the latter to uncover the determinants of the SI relation. Macroeconomic state variables such as openness, the age dependency ratio, government current and consumption expenditures are found to affect the SI relation significantly in the long run.
Keywords: E21; C23; C14; E22; 330; Saving-investment relation; Feldstein-Horioka puzzle; functional coefficient models; Feldstein-Horioka-Paradoxon; Offene Volkswirtschaft; Schätztheorie; Schätzung; Welt